2008
DOI: 10.1002/qsar.200730154
|View full text |Cite
|
Sign up to set email alerts
|

A Combined 2D‐ and 3D‐QSAR Study on Analogues of ARC‐111 with Antitumor Activity

Abstract: Two-Dimensional (2D) and Three-Dimensional (3D) Quantitative Structure -Activity Relationships (QSARs) of a series of analogues of ARC-111 with antitumor activity expressed as pIC 50 , which is defined as the negative value of the logarithm of necessary molar concentration of these compounds to cause 50% growth inhibition against tumor cell lines P388, have been studied by using a combined method of the DFT, MM2, and statistics for 2D, as well as the Comparative Molecular Field Analysis (CoMFA) for 3D. The est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Many studies uses only the r 2 to do so with the risk of QSAR over-fitting or over-estimation leading if their values are high;30,38 however, Thai et al and Liao et al show that the QSAR model with high r 2 value does not necessarily correlate with a good predictive model,39,40 and for classic QSAR studies, 95% confidence interval is commonly used for models validation. In our study, the 2D-QSAR model was determined as having a good ability to predict accurately based on an interval of confidence of 95% (blue dots for training set and red dots for prediction set in Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies uses only the r 2 to do so with the risk of QSAR over-fitting or over-estimation leading if their values are high;30,38 however, Thai et al and Liao et al show that the QSAR model with high r 2 value does not necessarily correlate with a good predictive model,39,40 and for classic QSAR studies, 95% confidence interval is commonly used for models validation. In our study, the 2D-QSAR model was determined as having a good ability to predict accurately based on an interval of confidence of 95% (blue dots for training set and red dots for prediction set in Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our stepwise MLR and PLS regression analyses, ClogP was not an important descriptor for antitumor activities against RPMI 8402 tumor cells to analogues of ARC-111. Stepwise regression and PLS study showed that the antitumor activity against RPMI was controlled mainly by electronic factors instead of hydrophobicity, which is different from the situation for cytotoxicity against P388 tumor cells (Liao et al, 2008). …”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…QSAR studies on cytotoxicity have given good results on small and homogeneous datasets. For instance Liao et al [2,3] or Chan et al [4] obtained models with good statistical quality (R 2 close to 0.9) for datasets ranging from 10 to 25 compounds. The main parameters used to model cytotoxicity have been for example water-octanol partition coefficient, which describes a compounds membrane permeability and molecular orbital energies that characterize reactivity [2,3,4].…”
Section: Introductionmentioning
confidence: 96%